2012
DOI: 10.1016/j.ccr.2012.03.043
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Tumor-Propagating Cells, Regional Tumor Heterogeneity, and Dynamic Cell Movements in Embryonal Rhabdomyosarcoma

Abstract: Summary Embryonal rhabdomyosarcoma (ERMS) is an aggressive pediatric sarcoma of muscle. Here, we show that ERMS-propagating potential is confined to myf5+ cells and can be visualized in live, fluorescent transgenic zebrafish. During early tumor growth, myf5+ ERMS cells reside adjacent normal muscle fibers. By late stage ERMS, myf5+ cells are reorganized into distinct regions separated from differentiated tumor cells. Time-lapse imaging of late stage ERMS revealed that myf5+ cells populate newly formed tumor on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
140
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(152 citation statements)
references
References 32 publications
12
140
0
Order By: Relevance
“…The animal studies were approved by the Massachusetts General Hospital Subcommittee on Research Animal Care under protocol #2012N000127 (zebrafish). Fluorescence-labeled ERMS were created by microinjecting the rag2: kRASG12D transgene into mylz2-mCherry transgenic, one-cell stage syngeneic zebrafish (13) and transplanted into 5-to 6-wk-old nonfluorescent, CG1-strain recipient fish (2.5 × 10 4 unsorted cells per fish, 2-μL volume). ERMSengrafted fish were imaged and then exposed to drug or DMSO vehicle in six-well plates (two fish per well, n = 4-8 animals per drug treatment).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The animal studies were approved by the Massachusetts General Hospital Subcommittee on Research Animal Care under protocol #2012N000127 (zebrafish). Fluorescence-labeled ERMS were created by microinjecting the rag2: kRASG12D transgene into mylz2-mCherry transgenic, one-cell stage syngeneic zebrafish (13) and transplanted into 5-to 6-wk-old nonfluorescent, CG1-strain recipient fish (2.5 × 10 4 unsorted cells per fish, 2-μL volume). ERMSengrafted fish were imaged and then exposed to drug or DMSO vehicle in six-well plates (two fish per well, n = 4-8 animals per drug treatment).…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish between the two possibilities, we took advantage of our myf5: GFP/mylz2:mCherry transgenic zebrafish line to label distinct subpopulations of ERMS cells according to their differentiation status in vivo. Our previous studies have shown that the myf5: GFP + /mylz2:mCherry − TPC population exclusively retains selfrenewal capacity, whereas late-differentiating myf5:GFP − /mylz2: mCherry + tumor cells lack both the capacity to self-renew and to metastasize (13,14). After 5-d drug treatment of animals engrafted with myf5:GFP/mylz2:mCherry expressing ERMS, relative proportions of ERMS cell subpopulations were assessed by FACS (n = 3 independent primary tumors).…”
Section: Gsk3 Inhibitors Activate the Wnt/β-catenin Pathway To Stimulatementioning
confidence: 99%
See 1 more Smart Citation
“…Once they have established a new tumor site, the less differentiated myf5-positive cells migrate into the newly forming tumor, ultimately driving tumor expansion and progression. 125,126 This implicates that the less differentiated RMSpropagating cells may take advantage of specific nutrients produced by the neighboring more differentiated cells during tumor dissemination, a process that might be even influenced by the proportion of fast or slow twitch muscle fibers potentially releasing specific metabolites around the tumor niche (at least when the tumor arises in muscle beds). This scenario seemingly resembles the so-called reverse Warburg effect, in which epithelial cancer cells were found to corrupt the stroma associated fibroblasts undergoing myo-fibroblastic differentiation to release micronutrients in the milieu, such as lactate and pyruvate, which are then taken up by cancer cells to produce energy in the mitochondria.…”
Section: Targeting Intratumor Cell Heterogeneity: a Difficult But Promentioning
confidence: 99%
“…Phenotypically and functionally distinct subsets of cells with differential ability to repopulate tumors in secondary recipients, to selfrenew, and to migrate were identified in models of fusion-negative RMS (Walter et al 2011;Ignatius et al 2012). However, potential differences in drug sensitivities between individual RMS cell subsets and their clonal evolution over time are not known.…”
Section: Critical Biological Problemsmentioning
confidence: 99%